Impact of vortex generator and two-phase MWCNT-MgO/water hybrid nanofluid on thermo-hydraulic performance and exergy and energy efficiency of a solar collector under Kuwait climatic conditions. (June 2023) - Alnaqi, Abdulwahab A.; Al-Rashed, Abdullah A.A.A.
Abstract: The effect of curved vortex generators and two-phase MWCNT-MgO/water hybrid nanofluid (HNF) on thermo-hydraulic performance and exergy and energy efficiency of a solar collector in a turbulent flow regime is examined in this study. The simulations performed for the climatic conditions of Kuwait. The two-phase DWCNT-MgO/water HNF is modeled using the mixture model. The numerical study is performed for DWCNT-MgO/water HNF with a volume fraction (φ) range of 1–3%, Reynolds number (Re) range of 5000–20, 000, and four Pitch Ratio (PR = 0 (Case A), PR = 0.1 (Case B), PR = 0.2 (Case C) and PR = 0.3 (Case D)). It is found that the average Nusselt number (Nuav ) and pressure drop (Δp) are enhanced with Re and φ. At φ = 3% and Re = 20, 000, placing the vortex generator with a PR = 0.3 (Case D) inside the solar collector causes the Nuav to improve by 83.09% as compared to the solar collectors without turbulators. In addition, the results demonstrated that the use of vortex generators is desirable in all PRs. For Case D and φ = 3%, the exergy efficiency is improved by 45.02% as Re is enhanced from 5000 to 20, 000.